﻿Chemical and biological properties of bio-active compounds from garlic (Allium sativum) - Aigerim Bazaraliyeva; Dias Moldashov; Aknur Turgumbayeva; Elmira Kartbayeva; Assem Kalykova; Lazzat Sarsenova; Raushan Issayeva (Pensoft Publishers, 2022)
Garlic (Allium sativum) is one of the oldest cultivated plants. It has been used as a spice, food, and folk medicine for many years. Garlic contains about 2000 biologically active components. For centuries, scientists have obtained a variety of compositions and physiological activities of garlic, depending on the methods of processing and extraction. Many review articles were published, where the object of the study was garlic. But there are very few broad literature reviews where garlic has been fully disclosed as a medicinal raw material. The study found that some garlic products and processing procedures were not standardized or tested for safety. A broad overview of this object can direct the attention of the scientific community in the right direction. This review contains various processing methods and yields from these extracts. In addition, most of the key physiological properties of the active substances of the raw materials are prescribed.